POLARESISTENCY OF SALMONELLA TYPHI BACTERIA TO ANTIBIOTIC CEFTRIAXONE AND CIPROFLOXACIN - Andre Budi; Novita Lina Sembiring (Journal Health & Science : Gorontalo Journal Health and Science Community, 2022)
Typhoid fever is an unbearable severe infection of the small digestive system, with the side effect of fever lasting up to seven days, and accompanied by stomach related disorders. Typhoid fever is a very common disease in Indonesia, both among clinical faculties and the population as a whole, and assuming that a child complains of fever, antimicrobials are the therapy of choice. Inappropriate use of various types of antibiotics, due to easy public access to drugs, will lead to an increase in the incidence of bacteria, including Salmonella typhi, which are resistant to ABRB (Antibiotic Resistant Bacteria) antibiotics. The type of research used in this study was Experimental Laboratory with a research design using the Disc Diffusion Method. This study aims to determine the resistance pattern of Salmonella typhi bacteria to Ceftriaxone and Ciprofloxacin antibiotics. This study aims to determine the resistance pattern of Salmonella typhi bacteria to Ceftriaxone and Ciprofloxacin antibiotics. The average value (mm) for 24 hours of ceftriaxone: 0.35, ciprofloxacin: 29,175 The average value (mm) for 48 hours of ceftriaxone: 14.8, ciprofloxacin: 29.4 Based on the results of the research data and images, it can be concluded that the diameter of the inhibition zone or clear zone of the salmonella typhi bacteria culture contained in petri dishes with MHA media on the ceftriaxone antibiotic was found to be an intermediate, which is a transition state from a drug resistant state but not completely resistant, while the ciprofloxacin antibiotic showed that the results were still sensitive to salmonella typhi bacteria. , with an average value of 14.8 and 29.4 mm where according to the CLSI (Clinical Laboratory Standards Institute) standard, the diameter of the bacterial inhibition zone is 17 mm, the intermediate category if the diameter of the bacterial inhibition zone is 14-16 mm, and the resistant category if the diameter of the bacterial inhibition zone is 14-16 mm. Bacterial inhibition zone is 13 mm.AbstrakDemam tifoid adalah infeksi hebat yang tak tertahankan pada system pencernaan kecil, dengan efek samping demam yang berlangsung hingga tujuh hari, dan disertai gangguan terkait perut. Penggunaan berbagai jenis antibiotik secara luas yang tidaktepat, akibat mudahnya akses masyarakat terhadap obat akan menyebabkan peningkatan kejadian bakteri, termasuk Salmonella typhi, yang resisten terhadap antibiotik ABRB (Antibiotic Resistant Bacteria. Jenis penelitian yang digunakan dalam penelitian ini adalah Eksperimental Laboratorium dengan rancangan penelitian menggunakan Metode Difusi Kertas Cakram (Disc Diffusion Method). Penelitian ini bertujuan untuk mengetahui polaresistensi bakteri Salmonella typhi terhadap antibiotik Ceftriaxone dan Ciprofloxacin.Penelitian ini bertujuan untuk mengetahui polaresistensi bakteri Salmonella typhi terhadap antibiotik Ceftriaxone dan Ciprofloxacin. Nilai rata-rata (mm) selama 24 jam ceftriaxone: 0,35 , ciprofloxacin : 29,175 Nilai rata-rata (mm) selam 48 jam ceftriaxone : 14,8 , ciprofloxacin : 29,4 Berdasarkan hasil data dan gambar penelitian dapat di simpulkan bahwa diameter zona hambat atau zona bening dari biakan bakteri salmonella typhi yang terdapat dalam cawan petri dengan media MHA pada antibiotik ceftriaxone ditemukan sebagai intermediate yaitu suatu keadaan transisi dari keadaan resisten obat tetapi tidak resisten sepenuhnya, sedangkan pada antibiotik ciprofloxacin menunjukkan hasil masih sensitive terhadap bakteri salmonella typhi , dengan nilai rata-rata 14,8 dan 29,4 mm dimana menurut standart CLSI (Clinical Laboratory Standards Institute), diameter zona hambat bakteri ≥ 17 mm, kategori intermediet apabila diameter zona hambat bakteri 14-16 mm, dan kategori resisten apabila diameter zona hambat bakteri yaitu ≤ 13 mm.